Predictions of watertable depth and soil salinity levels for land capability assessment using site indicator species - Bennett, Sarita; Barrett-Lennard (CSIRO Publishing, 2013)
Salt-affected land varies spatially and seasonally in terms of soil salinity and depth to the watertable. This paper asks whether native and naturalised species growing on saltland can be used as ‘indicators’ of saltland capability. The percentage cover of native and naturalised species was recorded in spring 2004 and 2005 across saltland transects on three sites in Western Australia. The presence of these plants was related to average soil salinity (ECe) at depth (25–50 cm), and depth to the watertable in spring. Eight naturalised species occurred with ≥40% cover on the sites. Species preferences varied, with some such as samphire (Tecticornia pergranulata) and puccinellia (Puccinellia ciliata) only occurring with shallow watertables (<0.7 m deep) and with ECe values >16 dS/m. Other species such as capeweed (Arctotheca calendula) and annual ryegrass (Lolium rigidum) were dominant where watertables were deeper (>1.3 m) and salinity levels lower (ECe values 2–8 and 4–16 dS/m, respectively). Our data suggest that some of the species recorded can be used as indicators of saltland capability and, further, can predict the most productive species to sow in that area. Other species were found not to be good indicators as they displayed more opportunistic habitat requirements.